Using Fan Fiction as Reading Material for Tenth Grader - Wulandari, Wahyu Dewi (RETAIN, 2022)
Reading is the most extensive and intensive skill. Most of learners usually read only a material book that given by government in the class. Some of learner may find the reading text is boring just by read the title. By looking at this situation, it is very important for them to read what they are interested in as a way to develop their reading interest. For example is introducing them to read Fan Fiction. This research is aimed to find out whether fan fictions effective as reading material for teaching English conducted at tenth grade of SMAN 3 Tuban. The researcher decides that this study use experimental research. The research focused on collecting numerical data to explain what was observed. The researcher decided to use Simple Random Sampling Procedure to choose the sample groups. Those groups are X MIA 1 and X MIA 2. The researcher applied Pretest–Posttest Control Group Design to both subjects and with the treatment (only for experimental class) for this study. The researcher give pre-test and treatment to the experimental class (X MIA 1), and in the end the researcher give post-test to accomplish this study. The researcher gets the data analyzed by the test in experimental class. It was analyzed by using Microsoft Office Excel in data analysis; paired sample test of t-test. The outcome of this study pointed out that there was a significant difference score between students score in experimental class that used fan fiction as material and controlled class that did not use fan fiction as reading material for tenth grade. Key Words: Fan Fiction, Reading Comprehension, Reading Material